Minimally Invasive High-Resolution Investigation of Site Form and Disturbance at Rat Island (AhGx-7), Cootes Paradise, Ontario. (17th February 2023) - Fletcher, Beatrice; Cannon, Aubrey; Martin, Scott; Reinhardt, Eduard
ABSTRACT: This paper presents a reinvestigation of archaeological material at Rat Island (AhGx-7), a proposed Princess Point period site in Cootes Paradise, Ontario, Canada. Applying a minimally invasive coring and augering strategy paired with soil properties and high-resolution multi-element chemical evaluation, we established that a low rise on the landscape, previously attributed to Princess Point or Woodland period occupation, is instead associated with the a.d. 1830s construction of the Desjardins Canal. Comparing the distribution of anthropogenically associated chemicals across Rat Island, our results suggest that the portion of the Island impacted by canal construction likely contained the most intense evidence for human occupation. Furthermore, the distributions of chemicals across undisturbed portions of Rat Island fail to support previously postulated settlement patterning models, suggesting instead a location of variable and potentially ephemeral occupation. This study establishes the utility of core and auger sampling and Itrax™ multi-element analysis when seeking to understand site formation, presenting an alternative to more time-consuming excavation strategies.